Health‐related quality of life of older Asian patients with multimorbidity in primary care in a developed nation. Issue 10 (31st August 2016) - Quah, Joanne Hui Min; Wang, Pei; Ng, Roderica Rui Ge; Luo, Nan; Tan, Ngiap Chuan
Abstract : Aim: Older adults are susceptible to two or more chronic ailments or multimorbidity. The present study aimed to establish the relationship between multimorbidity and health‐related quality of life (HRQoL) amongst Asian elderly patients in primary care in a developed nation. It also assessed how functional disability and chronic musculoskeletal pain are associated with HRQoL. Methods: A cross‐sectional study was carried out in a Singapore public primary care clinic. An interviewer‐administered questionnaire was used to collect data on chronic disease profile, HRQoL (using the European Quality of Life 5 Dimension), basic activities of daily living, instrumental activities of daily living, musculoskeletal pain and sociodemographic characteristics. The association of multimorbidity, functional disability and chronic musculoskeletal pain with HRQoL was assessed using multivariate linear regression analysis. Results: A total of 498 outpatients aged 65 years and older with multimorbidity were enrolled. Their mean age was 73.9 years, and approximately 75% had between two and four chronic conditions. The most commonly reported chronic conditions were hypertension (86.1%), hyperlipidemia (80.7%), diabetes (40.2%) and arthritis (33.3%). The European Quality of Life 5 Dimension index score decreased significantly when the number of comorbidities was more than five. Chronic hip and knee pain, one or more "dependent" activities of daily living dimensions and two or more "dependent" IADL dimensions were independently associated with worse HRQoL. Conclusions: Multimorbidity is associated with poorer HRQoL amongst older adults in Singapore. Review of chronic musculoskeletal pain and functional disabilities should be integrated into the comprehensive assessment of older adults in an enhanced model of primary care to improve the HRQoL of these older patients.Geriatr Gerontol Int 2017; 17: 1429–1437.